Quantification of Santonin From Artemisia Pallens Wall by HPTLC - A. RUIKAR; R. JADHAV; A.TAMBE; A. MISAR; A. MUJUMDAR; V. PURANIK; N. DESHPANDE (International Journal of Pharma and Bio Sciences, 2010)
In solubility determination, it was found that there is tremendous increase in solubility of naproxen in hydrotropic 0.5 M ibuprofen sodium solution. In the present investigation, solution of 0.5 M ibuprofen sodium (an economic hydrotropic agent) has been employed to solubilize a poorly water soluble drug naproxen for its titrimetric analysis. The results of analysis by proposed method are very comparable with those of British Pharmacopoeial method. The proposed method is new, rapid, simple and reproducible. The proposed method of analysis does not involve the use of an organic solvent, hence it is eco-friendly and safe method.